Burkholderia cenocepacia keratitis with exogenous endopthalmitis: a complex combination - Bahaman Shah, Nur Sakinah; Rosli, Abdul Hadi; Mohd. Kamal, Khairidzan; Nordin, Muhammad Faiz (Springer Nature, 2025)
In this report, we present a case of Burkholderia cenocepacia (B. cenocepacia) keratitis with exogenous endophthalmitis in a post-vitrectomy eye. The patient was a 68-year-old man with a history of treated corneal laceration and endophthalmitis who presented with acute pain, redness, and lid swelling affecting the left eye following working at a palm oil plantation. There was a paracentral corneal stromal infiltrate with dense vitritis in his left eye. Cornea cultures grew B. cenocepacia. He received two modalities of antimicrobials, including intravitreal injections and intensive topical antibiotics. Pars plana vitrectomy was not performed due to poor corneal visibility from a previous trauma scar. His stromal infiltrates and vitreous opacity responded to therapy that was sensitive to this organism, and the keratitis healed with scarring after a month. The progression of B. cenocepacia keratitis to endophthalmitis can be rapid. Early identification and appropriate commencement of antibiotics can prevent detrimental sequelae, including blindness and loss of the eyeball